Exploring the Relationship Between Sleep Apnea, Myocardial Infarct Size, and Coronary Collaterals in Acute Myocardial Infarction: A Multidisciplinary Study - Kundel V; Devarakonda K; Khan S; Suarez-Farinas M; Cohen O; Santos-Gallego C; Menegus MA; Kini A; Vengrenyuk Y; Okamoto N; Ueda H; Gidwani U; et al. (Nature and Science of Sleep)
Vaishnavi Kundel,1 Kavya Devarakonda,1 Samira Khan,1 Mayte Suarez-Farinas,1 Oren Cohen,1 Carlos Santos-Gallego,1 Mark A Menegus,2 Annapoorna Kini,1 Yuliya Vengrenyuk,1 Naotaka Okamoto,1 Hiroshi Ueda,1 Umesh Gidwani,1 Jorge R Kizer,3 Susan Redline,4 Robert Kaplan,2,5 Neomi Shah1 1Icahn School of Medicine at Mount Sinai, New York, NY, USA; 2Albert Einstein College of Medicine, Bronx, NY, USA; 3Cardiology Section, San Francisco Veterans Affairs Health Care System and Departments of Medicine, Epidemiology and Biostatistics, University of California San Francisco, San Francisco, CA, USA; 4Brigham and Women’s Hospital, Harvard Medical School, Boston, MA, USA; 5Public Health Sciences Division, Fred Hutchinson Cancer Research Center, Seattle, WA, USACorrespondence: Vaishnavi Kundel, Division of Pulmonary, Critical Care and Sleep Medicine, Department of Medicine, Icahn School of Medicine at Mount Sinai, One Gustave L Levy Place, Box 1232, New York, NY, 10029, USA, Tel +1-212-241-1967, Email Vaishnavi.kundel@mssm.eduPurpose: We designed a study investigating the cardioprotective role of sleep apnea (SA) in patients with acute myocardial infarction (AMI), focusing on its association with infarct size and coronary collateral circulation.Methods: We recruited adults with AMI, who underwent Level-III SA testing during hospitalization. Delayed-enhancement cardiac magnetic resonance (CMR) imaging was performed to quantify AMI size (percent-infarcted myocardium). Rentrop Score quantified coronary collateralization (scores 0– 3, higher scores indicating augmented collaterals). Group differences in Rentrop grade and infarct size were compared using the Wilcoxon Rank-Sum test and Fisher’s Exact test as appropriate, with a significance threshold set at p < 0.05.Results: Among 33 adults, mean age was 54.4± 11.5 and mean BMI was 28.4± 5.9. 8 patients (24%) had no SA, and 25 (76%) had SA (mild n=10, moderate n=8, severe n=7). 66% (n=22) underwent CMR, and all patients had Rentrop scores. Median infarct size in the no-SA group was 22% versus 28% in the SA group (p=0.79). While we did not find statistically significant differences, moderate SA had a trend toward a smaller infarct size (median 15.5%; IQR 9.23) compared to the other groups (no SA [22.0%; 16.8,31.8], mild SA [27%; 23.8,32.5], and severe SA [34%; 31.53], p=0.12). A higher proportion of moderate SA patients had a Rentrop grade > 0, with a trend toward significance (moderate SA versus other groups: 62.5% versus 28%, p=0.08).Conclusion: Our study did not find statistically significant differences in cardiac infarct size and the presence of coronary collaterals by sleep apnea severity among patients with AMI. However, our results are hypothesis-generating, and suggest that moderate SA may potentially offer cardioprotective benefits through enhanced coronary collaterals. These insights call for future research to explore the heterogeneity in ischemic preconditioning by SA severity and hypoxic burden to guide tailored clinical strategies for SA management in patients with AMI.Keywords: sleep apnea, MI, myocardial infarction, cardiac MRI, Rentrop, ischemic preconditioning